Perspectives on child education: montessori and Al-Ghazali - Abdul Razak, Mohd Abbas; Abdullah, Norillah (Department of Communication, KIRKHS, IIUM, 2024)
Childhood is characterized by innocence, exploration, and inquisitiveness. As young learners, children bravely embrace the trial-and-error approach to learning. The energy and curiosity displayed by children during their formative years marvel many parents and teachers alike. Here, we will explore some of the ideas about child education put forth by Maria Montessori (1870-1952) and Al-Ghazali (1058-1111). The concepts articulated by these two great educators—one from the West and the other from the East—hold significant relevance even in our modern, globalized world.